A Cluster of Fatal Tick-borne Encephalitis Virus Infection in Organ Transplant Setting. (4th April 2017) - Lipowski, Dariusz; Popiel, Marta; Perlejewski, Karol; Nakamura, Shota; Bukowska-Ośko, Iwona; Rzadkiewicz, Ewa; Dzieciątkowski, Tomasz; Milecka, Anna; Wenski, Wojciech; Ciszek, Michał; Dębska-Ślizień, Alicja; Ignacak, Ewa; et al.
Abstract: Background: Tick-borne encephalitis virus (TBEV) infection has become a major health problem in Europe and is currently a common cause of viral brain infection in many countries. Encephalitis in transplant recipients, althrough rare, is becoming a recognized complication. Our study provides the first description of transmission of TBEV through transplantation of solid organs. Methods: Three patients who received solid organ transplants from a single donor (2 received kidney, and 1 received liver) developed encephalitis 17–49 days after transplantation and subsequently died. Blood and autopsy tissue samples were tested by next-generation sequencing (NGS) and reverse transcription polymerase chain reaction (RT-PCR). Results: All 3 recipients were first analyzed in autopsy brain tissue samples and/or cerebrospinal fluid by NGS, which yielded 24–52 million sequences per sample and 9–988 matched TBEV sequences in each patient. The presence of TBEV was confirmed by RT-PCR in all recipients and in the donor, and direct sequencing of amplification products corroborated the presence of the same viral strain. Conclusions: We demonstrated transmission of TBEV by transplantation of solid organs. In such a setting, TBEV infection may be fatal, probably due to pharmacological immunosuppression. Organ donors should be screened for TBEV when coming from or visiting endemic areas.